Sensing of soil bulk density for more accurate carbon accounting - Lobsey, C. R.; Viscarra Rossel, R. A. (European journal of soil science, 2016)
Summary Measurements of soil bulk density can aid our understanding of soil functions and the effects of land use and climate change on soil organic carbon (C) stocks. Current methods for measuring bulk density are laborious and expensive, subject to errors and complicated by the need to measure below the soil surface. These shortcomings are emphasized when there is need to characterize the spatial (lateral and vertical) and temporal variation of soil bulk density and related properties. We developed a technique that combines gamma‐ray attenuation and visible–near infrared (vis–NIR) spectroscopy to measure ex situ the bulk density of 1‐m soil cores that are sampled freshly, wet and under field conditions. We found that the accuracy of the sensor measurements was similar to that of the conventional single‐ring method, but sensing is rapid, inexpensive, non‐destructive and practical. Sensing can be used to measure many soil cores efficiently at fine depth resolutions (e.g. every 2 cm along the core), thereby allowing effective characterization of spatial variation in both lateral and vertical directions. The measurements can be made in the field, on wet soil cores, which reduces the costs and errors associated with transport, handling, oven‐drying and laboratory measurements. We show that sensing of bulk density can be used to measure organic C stocks on either a fixed‐depth (FD) or cumulative soil mass (CSM) basis. Our sensing approach to measure bulk density meets all the requirements for inclusion in a well‐designed soil organic C accounting system; it provides accurate and verifiable data on the spatial variation of soil bulk density so that changes in C stocks might be attributed more accurately to changes in either bulk density or in C content. Highlights Proximal soil sensors enable practical, accurate, verifiable and inexpensive measurements of bulk density for C accounting. We describe a new sensing approach for measuring soil bulk density. Measurements are rapid, accurate, verifiable and can be made on wet soil under field conditions and to depth. Sensing enables measurements of C stocks using both fixed‐depth or cumulative soil mass.